Understanding and Implementing the Islamic Academic Culture of Unissula and the Tagline of Unissula in Sendangguwo, Semarang - Sholeh, Muhammad Muhtar Arifin; Nuridin, Nuridin (Indonesian Journal of Community Services, 2023)
This study aims to socialize Budai (Islamic Academic Culture) and the tag-line of Unissula (Sultan Agung Islamic University) – namely BMGKU (Bismillah Building Generation of Khaira Ummah) to the community and to explore how community members understand and practice these things. From this socialization and deepening, the community is expected to be more familiar with Unissula's vision, mission, and goals, so that they are interested in loving Unissula and appreciating Unissula. The problem that arises in this service program is that people do not understand and practice the Unissula (BMGKU) and Budai taglines. The methods used in this program are lectures, questionnaires, and observation. The data collected is qualitative data which includes data on understanding and practice of "Bismillah" (asmaul husna) and aspects of Khaira Ummah (faith, amar ma'ruf, nahi munkar). In addition, data on understanding and practice of Budai (thaharah movement, congregational prayers, Islamic clothing, social etiquette, and receiving guests) were also collected using these methods. This community service program will be very useful for the promotion of Unissula and the socialization of Budai and the tagline of Unissula (BMGKU) to the community. In addition, this service is a community development program to better understand and practice Islamic teachings, which include aqidah, worship, and morality. The people who are fostered so that they become Khaira Ummah are the embodiment of Faith and Taqwa. People who believe and fear Allah will get great blessings from Allah Swt (Surah al-A'raaf 7:96). The results of mentoring in community service show that the majority of respondents (more than 60%) understand and practice the concept of Budai and the Tag-line BMGKU. Finally, this service program produced a material module for the socialization of Budai and the tagline of Unissula (BMGKU), as well as for community development.